1992
DOI: 10.2307/2951567
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of the Centipede Game

Abstract: We report on an experiment in which individuals play a version of the centipede game. In this game, two players alternately get a chance to take the larger portion of a continually escalating pile of money. As soon as one person takes, the game ends with that player getting the larger portion of the pile, and the other player getting the smaller portion. If one views the experiment as a complete information game, all standard game theoretic equilibrium concepts predict the first mover should take the large pil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
430
4
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 595 publications
(450 citation statements)
references
References 14 publications
15
430
4
1
Order By: Relevance
“…However, many experiments have shown that people are not completely rational in this sense. For example, McKelvey and Palfrey (1992) have shown that in a traditional centipede game, participants do not behave according to the Nash equilibrium reached by backward induction. In this version of the game, the payoffs are distributed in such a way that the game-theoretic optimal strategy is to always end the game at the first move.…”
Section: Criticism Of Backward Inductionmentioning
confidence: 99%
“…However, many experiments have shown that people are not completely rational in this sense. For example, McKelvey and Palfrey (1992) have shown that in a traditional centipede game, participants do not behave according to the Nash equilibrium reached by backward induction. In this version of the game, the payoffs are distributed in such a way that the game-theoretic optimal strategy is to always end the game at the first move.…”
Section: Criticism Of Backward Inductionmentioning
confidence: 99%
“…We then turn to another well-known experiment inconsistent with selfishness and subgame perfection, the variation on grab-a-dollar studied by McKelvey and Palfrey [1992]. In this experiment a player may either grab or pass.…”
Section: Introductionmentioning
confidence: 99%
“…However, the structure of the game is such that there is little opportunity for transferring utility to or from other players. As a result we show that regardless of how altruism is distributed in the population, there exist equilibria in which the coefficient of altruism does not matter, and that consequently these equilibria are the same as the equilibria of the selfish model.We then turn to another well-known experiment inconsistent with selfishness and subgame perfection, the variation on grab-a-dollar studied by McKelvey and Palfrey [1992]. In this experiment a player may either grab or pass.…”
mentioning
confidence: 99%
“…Experimental studies of rationality in game theory include McKelvey and Palfrey (1992), who find that subjects frequently fail to choose the unique Nash equilibrium actions, although they are able to make fewer errors over time with learning. McKelvey and Palfrey (1995) suggest that such errors may be due to bounded rationality and that these errors can be modeled by using latent utility components that are not reflected in pecuniary payoffs.…”
mentioning
confidence: 99%